2013
DOI: 10.1111/j.1365-2702.2012.04246.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of a nurse‐led education and psychosocial programme for patients with chronic heart failure and their partners

Abstract: Aims and objectives This randomised controlled trial was conducted to estimate the cost-effectiveness of a nurse-led education and psychosocial support programme for patients with heart failure (HF) and their partners. Background There are few studies evaluating cost-effectiveness of interventions among HF patient–partner dyads. Methods Dyads randomised to the experimental group received nurse-led counselling, computer-based education and written materials aimed at developing problem-solving skills at two,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
0
20
0
12
Order By: Relevance
“…(Schwarz et al, 2008) In the five papers which reported secondary outcomes or primary outcome variables at a later time null findings were noted. (Agren et al, 2013;Agren et al, 2015;Liljeroos et al, 2015Liljeroos et al, , 2016Liljeroos, Agren, Jaarsma, & Stromberg, 2014a) These included outcomes such as quality adjusted life years, (Agren et al, 2013) carer tasks, burden or patient morbidity, Liljeroos et al, 2016) or non-sustaining differences at a subsequent measurement time. (Liljeroos et al, 2015;Liljeroos et al, 2014a) Deeper analysis identified perceived control, quality of life, preparedness to care, self-care, depression, social support and rehospitalization as the outcome variables with mixed (positive and null) findings (Table 3).…”
Section: Affective Outcomesmentioning
confidence: 99%
“…(Schwarz et al, 2008) In the five papers which reported secondary outcomes or primary outcome variables at a later time null findings were noted. (Agren et al, 2013;Agren et al, 2015;Liljeroos et al, 2015Liljeroos et al, , 2016Liljeroos, Agren, Jaarsma, & Stromberg, 2014a) These included outcomes such as quality adjusted life years, (Agren et al, 2013) carer tasks, burden or patient morbidity, Liljeroos et al, 2016) or non-sustaining differences at a subsequent measurement time. (Liljeroos et al, 2015;Liljeroos et al, 2014a) Deeper analysis identified perceived control, quality of life, preparedness to care, self-care, depression, social support and rehospitalization as the outcome variables with mixed (positive and null) findings (Table 3).…”
Section: Affective Outcomesmentioning
confidence: 99%
“…Cost-benefit analysis supports the more widespread implementation of some education program, 17 and also justify some programs are not cost-effective which should be further developed and modified. 18…”
Section: Nursing Ee On Education Programmentioning
confidence: 99%
“…Although there is not yet consensus on how and when to include family effects in economic evaluations, key decision makers, including those in the United Kingdom and the United States, have taken the position that relevant family effects should be included [23,24]. They have been considered only in limited contexts, including prevention of HIV transmission, using a net monetary benefit approach [25]; chronic heart failure, by summation of patient and carer quality-adjusted life-years (QALYs) [26]; children's vaccinations, taking carer QALYs and productivity losses into account [27][28][29]; and dementia, with patients and carers analyzed separately [30]. The inclusion of family effects might also affect the appropriate time horizon because the impact of children's problems could extend into the child's adulthood [31].…”
Section: Boundary Setting For Economic Evaluation In Pndmentioning
confidence: 99%